2007
DOI: 10.1103/physrevlett.99.247202
|View full text |Cite
|
Sign up to set email alerts
|

Nonperturbative Scaling Theory of Free Magnetic Moment Phases in Disordered Metals

Abstract: The crossover between a free magnetic moment phase and a Kondo phase in low dimensional disordered metals with dilute magnetic impurities is studied. We perform a finite size scaling analysis of the distribution of the Kondo temperature as obtained from a numerical renormalization group calculation of the local magnetic susceptibility and from the solution of the self-consistent Nagaoka-Suhl equation. We find a sizable fraction of free (unscreened) magnetic moments when the exchange coupling falls below a diso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 43 publications
3
39
0
Order By: Relevance
“…This is the subject of ongoing work and will be published elsewhere. 11 On the experimental side, the relevance of the distribution of the Kondo temperature to the low-temperature anomaly of the dephasing rate could be established by utilizing samples with lower diffusion constants, such as the lowmobility samples of AuPd, examined in Ref. 61 (see also Ref.…”
Section: Dephasing Due To Free Magnetic Moments In Disordered Mmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the subject of ongoing work and will be published elsewhere. 11 On the experimental side, the relevance of the distribution of the Kondo temperature to the low-temperature anomaly of the dephasing rate could be established by utilizing samples with lower diffusion constants, such as the lowmobility samples of AuPd, examined in Ref. 61 (see also Ref.…”
Section: Dephasing Due To Free Magnetic Moments In Disordered Mmentioning
confidence: 99%
“…The finite-size rescaling will be investigated in a future work using a more refined numerical technique. 11 It is important to remark that a finite-size scaling analysis was performed in Ref. 29 in the strong disorder limit only.…”
Section: B the Distribution Of Tkmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical exchange coupling. -Recently, it was shown that the distribution of the exchange couplings J nn′ results in a wide bimodal distribution of the Kondo temperature and free magnetic moments [9,19,20,21]. This was at first obtained by solving the 1-loop Nagaoka-Suhl equation (NSE) [22] of the Kondo model in the representation of the eigenstates of H 0 .…”
mentioning
confidence: 99%
“…where N I = D/∆ I is the number of localized states with a finite wave function amplitude at the magnetic impurity site [21].…”
mentioning
confidence: 99%